The Interaction of “Globalization” and Persian “Handicrafts”: An Analytical Investigation - Maghsoodi, Safoora; Nadalian, Ahmad (Journal of History Culture and Art Research, 2018)
Here is the dawn of a century in which Globalization has affected all aspects of human’s activities, including society, government, production, knowledge, culture, art, security, peace, justice and environment. Globalization has caused changes in public consideration of social relationships and everyday life. These social changes have led to significant and profound effects on popular “handicrafts” which is one of the vivid indicators of a nation’s culture. Globalization offers novel opportunities to handicrafts, yet it has presented some challenges to these crafts as well. The current study is aimed to investigate the interaction of globalization and Persian handicrafts, by a theoretical approach and analytical method. By studying the elements of globalization and Persian handicrafts, this research concludes handicrafts should not be a passive phenomenon towards this widespread process, but by taking advantages of the opportunities created by globalization and also by eliminating threats, Persian handicrafts could expose their multiple abilities to make a positive interaction with globalization.